HTML5 Advertising - Percival, John.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Web advertising is changing. What was once a predominantly Flash-based medium is making the switch to HTML5, with the benefit of a plug-in free environment giving a larger audience for ads, and better integration with the page they are featured on. We live in a time where marketers, designers, and developers are confused as to what they can and can$1 (Bt do on different devices, browsers, and operating systems. What better way to finally make sense of it all, than by stepping through the entire campaign process on your own terms? HTML5 Advertising will educate you on the whole digital advertising process from start to finish, and help you take advantage of new HTML5 features such as canvas, CSS3 animations, DOM events, audio and video, and offline storage. You'll also learn how to get around discrepancies in browser support with JavaScript and polyfills. You will be provided with tips and tricks to better optimize content across screens and make the most successful campaign with the lightest footprint possible, which is especially important when deploying to mobile devices. This book: Takes you through the advertising campaign process with HTML5 from design to delivery Provides in-depth knowledge into the digital advertising landscape and the HTML5 specification Communicates tips and tricks coming from Flash and ActionScript to HTML5, CSS3 and JavaScript. HTML5 Advertising equips you with the knowledge to attack cutting-edge, rich media projects with confidence and scale, while also learning the essentials to communicate to internal and external clients. HTML5 is here whether you like it or not, so why not jump in early and head down the path of building the future.s
Keywords: Computer science; Computer Science; Computer Science, general